2018
DOI: 10.4236/ojog.2018.814148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metformin on Endometrial Thickness and Subendometrial Flow Patterns in Anovulatory Patients with Polycystic Ovarian Syndrome

Abstract: Background: Polycystic ovarian syndrome (PCOS) is considered the commonest endocrinological disorder affecting reproductive aged women. PCOS compromises fertility through various pathways. These pathways include hyperandrogenism, insulin resistance and impedance of the uterine and endometrial blood flow. Metformin improves the blood flow to the endometrium. It acts by reducing androgen level and correction of insulin resistance. Endometrial vascular indices were evaluated in this study to evaluate endometrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A comprehensive review of seven randomized clinical trials involving 702 women unsuccessfully trying to become pregnant for a period of 6 months showed an increased clinical pregnancy rate after metformin treatment. Moreover, these studies confirmed that metformin therapy improved blood supply and the thickness of the endometrium in PCOS women [155]. Additionally, Johnson suggested that women with PCOS undergoing IVF should be treated with metformin to reduce the risk of ovarian hyperstimulation syndrome [156].…”
Section: Effect Of Metformin On Fertilitymentioning
confidence: 82%
“…A comprehensive review of seven randomized clinical trials involving 702 women unsuccessfully trying to become pregnant for a period of 6 months showed an increased clinical pregnancy rate after metformin treatment. Moreover, these studies confirmed that metformin therapy improved blood supply and the thickness of the endometrium in PCOS women [155]. Additionally, Johnson suggested that women with PCOS undergoing IVF should be treated with metformin to reduce the risk of ovarian hyperstimulation syndrome [156].…”
Section: Effect Of Metformin On Fertilitymentioning
confidence: 82%
“… 66 A study showed that metformin reduces luminal epithelial height, gland density, and endometrial thickness. 67 Metformin can directly increase vascular endothelial growth factor (VEGF) production and increase angiogenesis, blood flow and endometrial receptivity. 68 The results of a study showed an increment in the number of normal and cystic glands in the metformin group compared to PCOS while daughter and conglomerate glands showed a decline.…”
Section: Discussionmentioning
confidence: 99%